2009
DOI: 10.1002/jctb.2158
|View full text |Cite
|
Sign up to set email alerts
|

Batch treatment of liquid fraction of pig slurry by intermittent aeration: process simulation and microbial community analysis

Abstract: BACKGROUND: Manure treatment in intensive livestock farming is required to reduce the risk of negative environmental impacts by nitrogen disposal. Biological removal through intermittent aeration in a single bioreactor is a suitable method for this purpose. The characteristic operation based on the alternation of oxic/anoxic phases confers these systems with certain particularities in terms of process modelling and of understanding the microbial interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 51 publications
2
1
0
Order By: Relevance
“…On the other hand, total nitrogen and NH4 + -N were 3.2 g TN/L and 2.7 g NH4 + -N/L and 2.1 g TN/L and 1.9 g NH4 + -N/L for RW and TW, respectively. Similar concentrations for total solids (26.5-24.9 g TS/L) and total COD (18.7-30.1 g/L) were reported by Magrí et al (2009).…”
Section: Methodssupporting
confidence: 76%
“…On the other hand, total nitrogen and NH4 + -N were 3.2 g TN/L and 2.7 g NH4 + -N/L and 2.1 g TN/L and 1.9 g NH4 + -N/L for RW and TW, respectively. Similar concentrations for total solids (26.5-24.9 g TS/L) and total COD (18.7-30.1 g/L) were reported by Magrí et al (2009).…”
Section: Methodssupporting
confidence: 76%
“…The oxidation of ammonium to nitrate, conducted as shown mainly by Nitrosomonas sp., in the continuous aerated cathode (P.1) was one of the main processes taking place and, as a result, a high accumulation of nitrate was detected in the cathode chamber (169.4±0.21 mg N-NO3 -L -1 ). These results, and the finding of a potential denitrifying community, suggested that establishing nitrification-denitrification processes may be feasible if the cathode is submitted to aerobic-anoxic cycles, similary to a SBR reactor as already described elsewhere (Magrí et al, 2009).…”
Section: Mfc Operation and Nitrogen Dynamicssupporting
confidence: 72%
“…[1,2]. The nature of the SBR technology offers flexibility in operation (more degrees of freedom as compared with conventional systems) and higher degree of automation, two aspects that favor implementation of control strategies for SBR operation [3][4][5][6]. As a result, SBRs provide great potential to maintain efficient total nitrogen removal against external disturbances.…”
Section: Introductionmentioning
confidence: 97%